Chemistry of advanced environmental purification processes of water : fundamentals and applications - Sogaard, Erik (Elsevier, 2014)
Chemistry of Advanced Environmental Purification Processes of Water covers the fundamentals behind a broad spectrum of advanced purification processes for various types of water, showing numerous applications through worked examples. Purification processes for groundwater, soil water, reusable water, and raw water are examined where they are in use full-scale, as a pilot approach, or in the laboratory. This book also describes the production of ceramic particles (nanochemistry) and materials for the creation of filtration systems and catalysts that are involved. Uses chemistry fundamentals to.